PERANCANGAN KONSEP VISUAL GUIDED JOURNAL BAGI PENGGUNA USIA 19–24 TAHUN YANG MENGALAMI KESULITAN TIDUR : DESIGNING THE VISUAL CONCEPT OF A GUIDED JOURNAL FOR USERS AGED 19–24 EXPERIENCING SLEEP DIFFICULTIES - Komang Trisna Saraswati Sudharsana; I Nyoman Artayasa; Gede Pasek Putra Adnyana Yasa (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2026)
Designing the Visual Concept of a Guided Journal for Users Aged 19–24 Experiencing Sleep Difficulties This study explores the visual concept design of a guided journal intended to support young adults aged 19–24 in managing sleep difficulties. Sleep problems in this age group are often associated with excessive use of digital devices and unstructured pre-sleep habits, which highlights the need for alternative media that can facilitate reflective and calming routines before bedtime. The study aims to identify visual preferences and conceptual elements that align with the emotional and aesthetic needs of users aged 19–24 in the context of pre-sleep reflection. The research employs a qualitative descriptive method through a literature review, an online survey involving 73 respondents, and in-depth interviews with two extreme users who experience more intense sleep difficulties. The design process adopts a Design Thinking approach, focusing on the empathize, define, and ideate stages as a framework for exploring the visual concept. Survey results indicate that most respondents prefer a minimalist visual style, as it is perceived as calm, simple, and not overly stimulating. In terms of color, respondents tend to favor dark palettes associated with nighttime and tranquility. These findings indicate that users’ visual preferences tend to emphasize elements that support emotional comfort and the reduction of cognitive stimulation before sleep. This study provides a conceptual foundation in the form of user visual preference formulations that may serve as a reference for developing guided journal designs for young adults experiencing sleep difficulties.